MicroRNA miR-92a-3p regulates breast cancer cell proliferation and metastasis via regulating B-cell translocation gene 2 (BTG2). Issue 1 (1st January 2021) - Jinghua, Huang; Qinghua, Zhou; Chenchen, Chen; Lili, Chen; Xiao, Xu; Yunfei, Wang; Zhengzhe, An; Changxiu, Lin; Hui, Han
ABSTRACT: MicroRNAs (miRNAs) dysregulation contributes to tumorigenesis, and it is reported that abnormal miR-92a-3p expression participates in multiple cancers' occurrence and progression. This study focuses on miR-92a-3p's functions and regulatory mechanism in breast cancer (BC). The current study proved miR-92a-3p expression was enhanced in BC tissues and cells, and its high expression was related to increased TNM stage and larger tumor size of BC patients. Functionally, transfection of miR-92a-3p mimics facilitated BC cell proliferation and metastasis, yet transfection of miR-92a-3p inhibitors functioned oppositely. In addition, BTG2 was verified as a direct miR-92a-3p target in BC cells. This research indicated that miR-92a-3p facilitates BC cell proliferation and metastasis through repressing BTG2 expression. GRAPHICAL ABSTRACT: uf0001